Collective tactical behaviours in football from positional data - Low, B.; Rein, R.; Memmert, D. (spinfortec2020digital: 13. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 24.-25. September 2020 in Bayreuth, 2020)
Positional data has been used in football to improve our understanding of players` tactical behaviours (Memmert & Raabe, 2018). This study presents an overview of some collective tactical variables used in this body of research, and their translations to applied practice, based on a recent review (Low, Coutinho, Gonçalves, Rein, Memmert, & Sampaio, 2020). For effective translation from research to practice, tactical variables need to be contextualised, which can be achieved through analysis at match, group, dyadic, and individual levels, and distinguished between different phases of play.